Threatening stimuli elicit a sequential cardiac pattern in arthropods - Pérez Schuster, Verónica (2024)
In order to cope with the challenges of living in dynamic environments, animals rapidly adjust their behaviors in coordination with different physiological responses. Here, we studied whether threatening visual stimuli evoke different heart rate patterns in arthropods and whether these patterns are related with defensive behaviors. We identified two sequential phases of crab´s cardiac response that occur with a similar timescale to that of the motor arrest and later escape response. The first phase was modulated by low salience stimuli and persisted throughout spaced stimulus presentation. The second phase was modulated by high-contrast stimuli and reduced by repetitive stimulus presentation. The overall correspondence between cardiac and motor responses suggests that the first cardiac response phase might be related to motor arrest while the second to the escape response. We show that in the face of threat arthropods coordinate their behavior and cardiac activity in a rapid and flexible manner.